HASIL BELAJAR SISWA DALAM KETERAMPILAN MENULIS TEKS CERITA FANTASI MENGGUNAKAN MODEL DISCOVERY LEARNING BERBANTUAN CANVA - Siti Rofi'a Darojat; Diena San Fauziya; Mimin Sahmini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Student’s weak writing skills in writing activities became the backgroundof this study (Sahmini, etc. 2020, p. 125). One internal factor is lack of motivation for reading and heightened student laziness. The goal in this study is to see the result of students’ learning with canva using the discovery learning model in the skill of textual fantasy stories. Qualitative descriptive is the method employed in this study. Writing a fantasy text test became the key to a data gathering technique. The study was followed by 15 students VII a country junior high school teacher Cikalong 1 teacher’s grade 9’ and an average of90’s scored by three students, 83 marks made by four students, and an average of 75 students. Research revealed that the canva application for the skill of writing a fantasy text using the discovery learning model gets “very well” on the predicate.